Sexual Humorous Appeals in Advertising: A Moderated Mediation Approach - Armyrioti, Maria; Voutsa, Maria C.; Hatzithomas, Leonidas; Boutsouki, Christina (My University, 2018)
Sexual humorous appeals have been and in a sense still remain a controversial issue. Despite a slight increase in the use of sexual humor in advertising over the last decades, it remains a risky creative approach for advertisers as it divides the audience. Academic interest in sexual humorous advertising has focused on descriptive approaches about its density and use. To date, there is a lack of experimental research on the effectiveness of sexual humorous appeals. The present study looks into the effects of sexual humorous appeals on consumer’s attitude towards the ad and the brand at different levels of sexual conservatism. Our findings reveal that sexual humor may create high irritation toward the ad when the audience has moderate and high levels of sexual conservatism, which in turn leads to a negative attitude toward the ad (Aad) and brand (Abr). This moderated mediation effect is not apparent in audiences with low levels of sexual conservatism.
Keywords: Sexual humorous; Negative attitude